Revitalizing Montreal’s Industrial Fabric: A Case Study of the Pointe-du-Moulin and the Farine Five Roses Flour Mill. - Baudoux, Anthea Loane Hinanui (University of Waterloo, 2024)
This thesis explores the revitalization of Montreal's industrial fabric by examining the unique site of Pointe-du-Moulin and its famous "Farine Five Roses" flour mill. This pier is known for being home to numerous flour mills, key structures that have influenced architects around the world with their monumental scale and simple forms. Flour mills played an essential role in shaping North America's urban fabric, communities and society. However, these landmark structures have disappeared from the cities' landscape, leaving only a few flour mills remaining in Canada. Most of these mills have been demolished, abandoned or relocated as cities expand into their industrial zones. These areas, often considered to be neglected and not accessible to the public, seem to be an ideal option for new residential development. This is especially apparent in Montreal, where Pointe-du-Moulin is now at the heart of a new urban redevelopment called "Bridge-Bonaventure". This development will lead to the demolition of numerous industrial buildings, giving little space and attention to the renowned Farine Five Roses flour mill. This thesis emphasizes the importance of flour mills in North America and proposes an urban design strategy that integrates and creates a public identity around the Farine Five Roses flour mill in Montreal. This thesis aims to preserve this industrial site's unique character and create a development unique to Montreal. The preservation of this flour mill will demonstrate that this industry can coexist with residential housing while enriching life on the pier and creating a common identity. This approach will revive these structures' historical and cultural values while meeting the city's future needs.
Keywords: Montreal; Architecture; Urban Planning; Pointe-du-Moulin; Flour Mills; industrial site; revitalization; preservation; housing